ASTHENOPIA AND ITS CORRELATION IN USING LAPTOP DURATION OF TARUMANAGARA UNIVERSITY STUDENTS - CESSILIA NAFILEITA JAUHARY, MINERVA; RASYID, MERIANA; IRAWATI, ENNY (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2024)
The COVID-19 pandemic has caused the use of electronic devices since many activities have moved online. The use of computers (desktops), tablets, laptops or other electronic devices (smartphones or e-book readers) has increased the incidence of asthenopia. This study aims to determine the incidence rate of eye fatigue or asthenopia for students in UNTAR Medicine and Engineering Faculties, as well as to compare the incidence rate among students in both faculties to recognize the relationship between the duration of laptop use and the incidence of asthenopia. Three hundred forty-seven respondents from the Faculties of Medicine and Engineering, class of 2019-2021, who had studied for at least five months. The prevalence of asthenopia in the Faculty of Medicine is 86,26%, and in the Faculty of Engineering is 82,35%, with a total of 85,30% in both faculties. There is no difference in the incidence of asthenopia between students of the Faculty of Medicine and the Faculty of Engineering, University of Tarumanagara. During online learning, 98,10% of students from the Faculty of Medicine and 92,94% from the Faculty of Engineering spent >2 hours studying using a laptop. In addition, the results show that there is no significant difference between symptoms and time staring at a laptop screen. The Chi-Square test results revealed a significance value of 0.122. It means there is no correlation between the length of time staring at a laptop screen and asthenopia symptoms.